Characterization of expanded austenite developed on AISI 316L stainless steel by plasma carburization - García Molleja, Javier (2010)
Expanded austenite generation through ion carburizing of AISI 316L using two different reactive gas mixtures (Ar 50%, H2 45%, CH4 5% and Ar 80%, H2 15%, CH4 5%) has been studied. It was found that an 14 µm surface layer of expanded austenite was developed with 30 min processing for both gas mixtures. Nevertheless, AES analyses have shown that on the 150 nm surface layer carbon in a concentration of 12% was diffused and located as carbide. For longer periods of processing, while for the gas mixture with 50% of Ar no significant modifications within those 150 nm surface layer were produced, for the gas mixture with 80% of Ar a gradual increase in the carbon concentration with time was found, with the extra carbon remaining as free carbon. The difference between both situations can be attributed to the different resulting current densities that have been of 7.0 mA cm−2 and 8.1 mA cm−2 for 50% and 80% of Ar respectively. Higher current densities result in higher carbon and Ar ions fluxes inducing, from one side surface element concentration modification through sputtering, and from the other the enhancement of carbon diffusion on the first hundred nanometers of the surface layers. This free carbon on top of the surface layers can act as solid lubricant reducing wear rate. Nevertheless, and in spite of the fact that expanded austenite was proved to be corrosion resistant, a reduction against NaCl solution corrosion in relation to the base material was observed. This lost to corrosion resistance can be attributed to carbide development on the layers closer to the surface that can work as a trigger for localized corrosion.